Effects of water movement and temperature on Rhizophydium infection of Planktothrix in a shallow hypereutrophic lake - Wagner, Ryan S.; McKindles, Katelyn M.; Bullerjahn, George S. (Frontiers in Microbiology, 2023)
Grand Lake St. Marys (GLSM) is a popular recreational lake located in western Ohio, USA, generating nearly $150 million in annual revenue. However, recurring algal blooms dominated by Planktothrix agardhii, which can produce harmful microcystin toxins, have raised concerns about water safety and negatively impacted the local economy. Planktothrix agardhii is host to a number of parasites and pathogens, including an obligate fungal parasite in the Chytridiomycota (chytrids). In this study, we investigated the potential of these chytrid (Rhizophydium sp.) to infect P. agardhii blooms in the environment by modifying certain environmental conditions thought to limit infection prevalence in the wild. With a focus on temperature and water mixing, mesocosms were designed to either increase or decrease water flow compared to the control (water outside the mesocosm). In the control and water circulation mesocosms, infections were found infrequently and were found on less than 0.75 % of the Planktothrix population. On the other hand, by decreasing the water flow to stagnation, chytrid infections were more frequent (found in nearly 3x as many samples) and more prevalent, reaching a maximum infection rate of 4.12 %. In addition, qPCR coupled with 16S - 18S sequencing was utilized to confirm the genetic presence of both host and parasite, as well as to better understand the effect of water circulation on the community composition. Statistical analysis of the data confirmed that chytrid infection was dependent on water temperature, with infections predominantly occurring between 19 – 23 °C. Additionally, water turbulence can significantly reduce the infectivity of chytrids, as infections were mostly found in stagnant mesocosms. Further, decreasing the water circulation promoted the growth of the cyanobacterial population, while increasing water agitation promoted the growth of green algae (Chlorophyta). This study starts to explore the environmental factors that affect chytrid pathogenesis which can provide valuable insights into controlling measures to reduce the prevalence of harmful algal blooms and improve water quality in GLSM and similarly affected waterbodies.